A targeted lipidomics workflow for high-throughput phenotyping and mechanism-based in vitro hepatotoxicity studies - Tzu-Hsin Yen; Chander K. Negi; Courtney Sakolish; Erin S. Baker; Ivan Rusyn (Toxicology in Vitro, 2026)

Understanding the brown planthopper (Nilaparvata lugens Stål) resistance in rice through biological and biochemical responses - Darshana Brahma; S. Rajna; Subhash Chander; C.N. Rajarushi; Ranjith Kumar Ellur; Jessa Joseph (Crop Protection, 2026)

In vitro evaluation of the immunostimulatory effects of PAM2CS lipopeptide-based TLR2 agonists in chicken peripheral blood mononuclear cells - Maramreddy Darshini; Saravanan Ramakrishnan; Firdous Ahmed; Deshkanwar S. Brar; Arshpreet Kaur; Deepak B. Salunke; Vishal Chander; Mithilesh Singh (Veterinary Research Communications, 2026)

Interactive Effects of Elevated CO2, Temperature, and Weed Competition on Mungbean - Dasari Sreekanth; Deepak Vishwanath Pawar; Rajeev Kumar; Shobha Sondhia; P. K. Singh; J. S. Mishra; Ankita Sinha; Subhash Chander; Nagaraju Mukkamula; B. Kiran Kumar (Agricultural Research, 2026)

Heterologous expression, purification and functional characterization of recombinant serratiopeptidase from Serratia marcescens AD-W2 - Devtulya Chander; Diksha Koul; Shubham Singh; Ravi S. Manhas; Diljeet Kumar; Sanket Shukla; Ravi P. N. Mishra; Zabeer Ahmed; Asha Chaubey (World Journal of Microbiology and Biotechnology, 2026)

Molecular detection and pathological evaluation of canine adenovirus 1 in Indian bear species - Karikalan M; Vishal Chander; Gaurav K. Sharma; Ilayaraja S; Ajeet Kumar Pandey; Sonalika Mahajan; Arun A. Sha; Parag Nigam; AM Pawde; Vivek Kumar Gupta; AK Sharma (Archives of Virology, 2026)

Evaluation of SWOT Beta Geophysical Products in the Indian Region During CAL-VAL Phase over the Land and Oceans - Aditya Chaudhary; Shard Chander; Arun Kumar Surisetty; Ritesh Agrawal; Neeraj Agarwal; Praveen Kumar Gupta; Raj Kumar; Rashmi Sharma; R. Venkat Shesu; T. V. S. Udaya Bhaskar; E. Pattabhi Rama Rao (Journal of the Indian Society of Remote Sensing, 2025)

Temporal variations in heavy metal concentrations in the Krishna river: a comprehensive seasonal assessment - R. Laxmi; R. Singh; A. Kumar; S. Chander; R. Haldhar; H. Almujibah (International Journal of Environmental Science and Technology, 2025)

A Global Analysis of Cases of Mucormycosis Recorded in the European Confederation of Medical Mycology / International Society for Human and Animal Mycology (ECMM / ISHAM) Zygomyco.net Registry from 2009 to 2022 - Anna Skiada; Maria Drogari-Apiranthitou; Emmanuel Roilides; Jagdish Chander; Sofya Khostelidi; Nikolai Klimko; Petr Hamal; Vanda Chrenkova; Souha S. Kanj; Saeed El Zein; Katrien Lagrou; Cornelia Lass-Flörl; et al. (Mycopathologia, 2025)

Spatial genetic structure of the endangered Himalayan Yew (Taxus wallichiana Zucc.): conservation implications in the Western Himalayas - Rajendra K. Meena; Maneesh S. Bhandari; Shivani Rohilla; Haripriya Kavidayal; Anita Rawat; Shanti; Chander Shekhar; Santan Barthwal; Harish S. Ginwal (Genetic Resources and Crop Evolution, 2025)

Functional response of temperature tolerant and control strain of Aenasius arizonensis against different densities of Phenacoccus solenopsis Tinsley - Kirankumar G N; Sachin S. Suroshe; Chaitanya M; K. Srinivas; Keerthi M C; Subhash Chander (Phytoparasitica, 2025)

Distribution and DNA Barcodes of Endophytic Fungi From Mangrove Roots of South Andaman Island - Madhusudan Thorati; S. Sai Elangovan; M. Punnam Chander; Jayant Kumar Mishra (Marine Ecology, 2025)
This study investigates the diversity of endophytic fungi associated with mangrove roots along the Sri Vijaya Puram coast, South Andaman. Root samples were collected from five stations between July 2014 and July 2016. A total of 256 fungal isolates were obtained from 637 root segments, with the highest diversity ( H ′ = 2.276) recorded in the stilt roots of Rhizophora apiculata . Fungal identification was performed using morphological characteristics and ITS region‐based molecular methods, with sequences compared to entries in the NCBI GenBank database using BLAST, revealing that most isolates belonged to the phylum Ascomycota. The detailed findings emphasize the ecological significance of mycobiota associated with mangrove roots, suggesting their potential role in nutrient cycling and contribution to ecosystem stability in the coastal waters of South Andaman.

SSR marker-based characterization of the timberline Himalayan Birch (Betula utilis D. Don) for genetic diversity and population structure - Rajendra K. Meena; Maneesh S. Bhandari; Shivani Rohilla; Haripriya Kavidayal; Anita Rawat; Shanti Saroj; Chander Shekhar; Santan Barthwal; Shailesh Pandey; Harish S. Ginwal (The Nucleus, 2025)

Influence of coloured shade nets on shoot and root growth of dragon fruit stem cuttings - Ajaypartap Singh; Subhash Chander; J. S. Brar (Vegetos, 2025)

Fusion of MobileNet and GRU: Enhancing Remote Sensing Applications for Sustainable Agriculture and Food Security - Ushus. S. Kumar; B. Suresh Chander Kapali; A. Nageswaran; K. Umapathy; Pradeep Jangir; K. Swetha; M. Amina Begum (Remote Sensing in Earth Systems Sciences, 2025)

Genetic evaluation of early reproductive traits of Harnali sheep - Spandan Shashwat Dash; Yogesh C. Bangar; Ankit Magotra; C. S. Patil; Dipin Chander Yadav; Parth Gaur; Z. S. Malik (Tropical Animal Health and Production, 2024)

Development of novel faba bean (Vicia faba L.) for release as a new cultivar with high yield and protein content - Rajesh K. Arya; Gajraj S. Dahiya; Ravi Kumar; Ranjeet K. Gill; Jitender K. Tiwari; Chander B. Yadav; Hanuman L. Raiger; Sandeep Kumar; Surya Kant (Genetic Resources and Crop Evolution, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

Enhancement of nutritional quality in maize grain through QTL-based approach - Pardeep Kumar; Ningthai Longmei; Mukesh Choudhary; Mamta Gupta; Bhupender Kumar; B. S. Jat; Bharat Bhushan; Manesh Chander Dagla; Sumit Kumar Aggarwal (Cereal Research Communications, 2024)

Wheat as a new host for potato aphid Macrosiphum euphorbiae Thomas (Hemiptera: Aphididae) and construction of its age-stage two-sex life tables - Y. N. Venkatesh; S. Rajna; Sachin S. Suroshe; Sunil Joshi; Subhash Chander (Cereal Research Communications, 2024)

Population genetic structure of a timberline oak (Quercus semecarpifolia Sm.) of western Himalayas and conservation implications - Harish S. Ginwal; Anita Rawat; Chander Shekhar; Maneesh S. Bhandari; Haripriya Kavidayal; Rajeev Shankhwar; Abhishek Yadav; Rama Kant; Santan Barthwal; Rajendra K. Meena (Conservation Genetics, 2024)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Spatial distribution and optimum sample size for monitoring of water lily aphid Rhopalosiphum nymphaeae (L.) in Makhana Euryale ferox Salisb - Vinod K. Padala; N Ramya; Manoj Kumar; S Rajna; Mandla Rajashekhar; YN Venkatesh; SM Raut; Subhash Chander; IS Singh; Mohd. Monobrullah (International Journal of Tropical Insect Science, 2023)

Sustainability Assessment of Rice-Wheat System Through Organic Fertilizers and Green Manuring in Sub-Tropical Humid Climate - Subhash Chander; S. C. Tripathi; Karnam Venkatesh; Neeraj Kumar; R. P. Meena; R. S. Chhokar; Nidhi Kamboj; Nitesh Kumar (International Journal of Plant Production, 2023)

Optimization of Potato Sprout Orientation Angle and Effective Weed Management Practice to Produce Higher Economical Tuber Yield from Cut Tuber Planting - C. R. Chethan; V. K. Tewari; A. K. Shrivastava; B. Nare; S. P. Kumar; R. P. Dubey; P. K. Singh; D. Ghosh; S. Chander; D. Sreekanth (Potato Research, 2023)

Deciphering host plant resistance mechanisms of rice genotypes resistant against Brown Planthopper - Prabhulinga Tenguri; Subhash Chander; Ranjith K. Ellur; P. S. Arya; Yogesh Yele (Euphytica, 2023)

On assessing the influence of a newly impounded reservoir on a nearby normal fault using a simple three-dimensional model of subsurface geological heterogeneity - Ramesh Chander; S K Tomar (Journal of Earth System Science, 2022)

Lipid- and TPGS-Based Core–Shell-Type Nanocapsules Endowed with High Paclitaxel Loading and Enhanced Anticancer Potential - Sameer S. Katiyar; Ravindra Patil; Rohan Ghadi; Kaushik Kuche; Varun Kushwah; Chander Parkash Dora; Sanyog Jain (AAPS PharmSciTech, 2022)

Spatio-temporal distribution of broad-leaved Quercus semecarpifolia indicates altitudinal shift in northwestern Himalayas - Chander Shekhar; Harish S. Ginwal; Rajendra K. Meena; Rajeev Shankhwar; Marco Antonio Caçador Martins-Ferreira; Shailesh Pandey; Santan Barthwal; Maneesh S. Bhandari (Plant Ecology, 2022)

A study to improve the fog/visibility forecast at IGI Airport, New Delhi during the winter season 2020–2021 - S H Arun; Charan Singh; Sebin John; Sumant Kumar Diwakar; Dinesh Kumar Sankhala; Narendra Nigam; Chander S Tomar; Gajendra Kumar (Journal of Earth System Science, 2022)

MN/CA9 gene expression as a potential tumor marker for renal cell carcinoma - Pamposh Raina; S. K. Singh; Anil K. Goswami; Manoj Kumar Kashyap; Madhu Khullar; S. K. Sharma; Kailash Chander Barwal (Molecular and Cellular Biochemistry, 2022)

Interactions of six spotted ladybird beetle, Cheilomenes sexmaculata (F.) with its host Phenacoccus solenopsis Tinsley and Intraguild members - Geethu S.; Sachin S. Suroshe; Subhash Chander; Venkanna Y. (International Journal of Tropical Insect Science, 2022)

Feeding potential and foraging behaviour of Cheilomenes sexmaculata (F.) on the cotton aphid, Aphis gossypii glover - Y. Venkanna; Sachin S. Suroshe; Subhash Chander; Sweetee Kumari (International Journal of Tropical Insect Science, 2021)

Isolation and genetic characterization of canine adenovirus type 2 from a domestic dog showing neurological symptoms - Vishal Chander; G. K. Sharma; Mukesh Bhatt; Sukdeb Nandi; S. Mahajan; Mithilesh Singh; K. Mahendran; M. Karikalan; Abhijit M. Pawde; Vikas Gupta; K. P. Singh; K. K. Rajak; et al. (Brazilian Journal of Microbiology, 2021)

Conservational Tillage and Weed Management Practices Enhance Farmers Income and System Productivity of Rice–Wheat Cropping System in Central India - Dibakar Ghosh; C. R. Chethan; Subhash Chander; Bhumesh Kumar; R. P. Dubey; H. S. Bisen; S. K. Parey; P. K. Singh (Agricultural Research, 2021)

Assessing the risk of mango quarantine pest Deanolis sublimbalis Snellen under different climate change scenarios - Gundappa Baradevanal; Subhash Chander; P. D. Kamala Jayanthi; H. S. Singh; D. Srinivasa Reddy (Journal of Plant Diseases and Protection, 2021)

Landless animal and poultry production prospects: an overview on feeding and sustainability with special reference to fruit and vegetable wastes (FVWs) - Mahesh Chander; M. S. Kannadhasan (Organic Agriculture, 2021)

Microspore derived population developed from an inter-specific hybrid (Brassica oleracea × B. carinata) through a modified protocol provides insight into B genome derived black rot resistance and inter-genomic interaction - Reeta Bhatia; Kanika Sharma; Chander Parkash; Achintya Pramanik; Dinesh Singh; Saurabh Singh; Raj Kumar; S. S. Dey (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

QTLs in salt rice variety CSR10 reveals salinity tolerance at reproductive stage - Preeti Pundir; Ashwanthi Devi; S. L. Krishnamurthy; Parbodh Chander Sharma; N. M. Vinaykumar (Acta Physiologiae Plantarum, 2021)

Isolation and Characterization of Serratiopeptidase Producing Bacteria from Mulberry Phyllosphere - Diksha Koul; Devtulya Chander; Ravi S. Manhas; Asha Chaubey (Current Microbiology, 2021)

Alterations of hemogram, serum biochemistry, oxidative/nitrosative balance, and copper/zinc homeostasis in dromedary camels naturally infected with poxvirus - U. K. De; V. Chander; Akhilesh; S. Mahajan; G. K. Sharma; Sukdeb Nandi; K. P. Singh; V. K. Gupta (Tropical Animal Health and Production, 2020)

Rice GWAS reveals key genomic regions essential for salinity tolerance at reproductive stage - Arvinder Singh Warraich; S. L. Krishnamurthy; Balwinder Singh Sooch; N. M. Vinaykumar; B. M. Dushyanthkumar; Jayakumar Bose; Parbodh Chander Sharma (Acta Physiologiae Plantarum, 2020)

Population structure of Alternaria species causing leaf blight of sunflower (Helianthus annuus L.) in India - M. Santha Lakshmi Prasad; N. Naresh; K. Sujatha; D. Usha; M. Sujatha; C. Sarada; S. Chander Rao; P. Chowdappa (Phytoparasitica, 2020)

Prediction Mapping Through Maxent Modeling Paves the Way for the Conservation of Rhododendron arboreum in Uttarakhand Himalayas - Maneesh S. Bhandari; Rajendra K. Meena; Rajeev Shankhwar; Chander Shekhar; Jalaj Saxena; Rama Kant; Vijay V. Pandey; Santan Barthwal; Shailesh Pandey; Girish Chandra; Harish S. Ginwal (Journal of the Indian Society of Remote Sensing, 2020)

Design and Toxicity Evaluation of Novel Fatty Acid-Amino Acid-Based Biocompatible Surfactants - Sameer S. Katiyar; Varun Kushwah; Chander Parkash Dora; Ravindra Y. Patil; Sanyog Jain (AAPS PharmSciTech, 2019)

A unique strategy to improve the floral traits and seed yield of Brassica oleracea cytoplasmic male sterile lines through honey bee-mediated selection - S. S. Dey; R. Bhatia; Achintya Pramanik; Kanika Sharma; Chander Parkash (Euphytica, 2019)

Frequent introgression of European cauliflowers in the present day cultivated Indian cauliflowers and role of Indian genotypes in the evolution of tropical cauliflower - S. S. Dey; R. Bhatia; Kanika Sharma; Ila Bhardwaj; Chithra Devi Pandey; Chander Parkash; Raj Kumar (Euphytica, 2019)

Genetic engineering of sunflower (Helianthus annuus L.) for resistance to necrosis disease through deployment of the TSV coat protein gene - Vasavi Singareddy; Vijay Reddy Sheri; Tarakeswari Muddanuru; Revathi Tatineni; Rakesh Kumar Jain; Chander Rao Sankaraneni; Varaprasad S. Kodeboyina; Sujatha Mulpuri (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Quantification of Antioxidant Contents in Sweet Pepper as Influenced by Planting Time and Fruit Picking Stage - Vinod K. Sharma; Chandresh Chandel; Raj Kumar; S. S. Dey; Chander Parkash; Reeta Bhatia; M. Mawliya (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Organic Agriculture 3.0 is innovation with research - Gerold Rahmann; M. Reza Ardakani; Paolo Bàrberi; Herwart Boehm; Stefano Canali; Mahesh Chander; Wahyudi David; Lucas Dengel; Jan Willem Erisman; Ana C. Galvis-Martinez; Ulrich Hamm; Johannes Kahl; et al. (Organic Agriculture, 2017)

Variability in residual feed intake and nutrient utilization in Murrah buffalo heifers - Tegene Negesse; Chander Datt; S. S. Kundu (Tropical Animal Health and Production, 2016)

On a model simulating lack of hydraulic connection between a man-made reservoir and the volume of poroelastic rock hosting the focus of a post-impoundment earthquake - Ramesh Chander; S K Tomar (Journal of Earth System Science, 2016)

Optimizing protocol for efficient microspore embryogenesis and doubled haploid development in different maturity groups of cauliflower (B. oleracea var. botrytis L.) in India - R. Bhatia; S. S. Dey; Shritika Sood; Kanika Sharma; V. K. Sharma; Chander Parkash; Raj Kumar (Euphytica, 2016)

Effect of Sowing Date and Cultivars on Aphid Infestation in Wheat with Climate Change Adaptation Perspective - Subhash Chander; Mazhar Husain; Vishwa Pal; Himanshu Pathak; S. D. Singh; Ramesh Harit; Vinod Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Ice Height and Backscattering Coefficient Variability over Greenland Ice Sheets Using SARAL Radar Altimeter - S. Chander; S. K. Mishra; Prakash Chauhan; Ajai (Marine Geodesy, 2015)

Waveform Classification and Water-Land Transition over the Brahmaputra River using SARAL/AltiKa & Jason-2 Altimeter - Shruti Desai; S. Chander; D. Ganguly; Prakash Chauhan; P. D. Lele; M. E. James (Journal of the Indian Society of Remote Sensing, 2015)

Mycological Profile and Antifungal Susceptibility of Fungal Isolates from Clinically Suspected Cases of Fungal Rhinosinusitis in a Tertiary Care Hospital in North India - Ruby Jain; Surinder K. Singhal; Nidhi Singla; Rajpal S. Punia; Jagdish Chander (Mycopathologia, 2015)

Inter specific hybridization (Brassica carinata × Brassica oleracea) for introgression of black rot resistance genes into Indian cauliflower (B. oleracea var. botrytis L.). - S. S. Dey; Kanika Sharma; R. Bhatia Dey; G. M. Sandeep Kumar; Dinesh Singh; Raj Kumar; Chander Parkash (Euphytica, 2015)

An integral-free expression for short-term changes in fault stability due to pore pressure induced when a point load is placed on the pervious boundary of a porous elastic half space containing a fault - Ramesh Chander; S K Tomar (Journal of Earth System Science, 2014)

De novo design and in-silico studies of novel 1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid derivatives as HIV-1 reverse transcriptase inhibitors - Ashok Penta; Subhash Chander; S. Ganguly; S. Murugesan (Medicinal Chemistry Research, 2014)

Genetic combining ability and heterosis for important vitamins and antioxidant pigments in cauliflower (Brassica oleracea var. botrytis L.) - S. S. Dey; Neeraj Singh; R. Bhatia; Chander Parkash; Chandresh Chandel (Euphytica, 2014)

Radiometric and geometric assessment of data from the RapidEye constellation of satellites - G. Chander; M.O. Haque; A. Sampath; A. Brunn; G. Trosset; D. Hoffmann; S. Roloff; M. Thiele; C. Anderson (International Journal of Remote Sensing, 2013)

Pathogen-derived resistance using a viral nucleocapsid gene confers only partial non-durable protection in peanut against peanut bud necrosis virus - S. Chander Rao; P. Bhatnagar-Mathur; P. Lava Kumar; A. Sudarshan Reddy; Kiran K. Sharma (Archives of Virology, 2013)

Erratum to: Phylogenetic framework and molecular signatures for the class Chloroflexi and its different clades; proposal for division of the class Chloroflexi class. nov. into the suborder Chloroflexineae subord. nov., consisting of the emended family Oscillochloridaceae and the family Chloroflexaceae fam. nov., and the suborder Roseiflexineae subord. nov., containing the family Roseiflexaceae fam. nov. - Radhey S. Gupta; Pranay Chander; Sanjan George (Antonie van Leeuwenhoek, 2013)

Phylogenetic framework and molecular signatures for the class Chloroflexi and its different clades; proposal for division of the class Chloroflexi class. nov. into the suborder Chloroflexineae subord. nov., consisting of the emended family Oscillochloridaceae and the family Chloroflexaceae fam. nov., and the suborder Roseiflexineae subord. nov., containing the family Roseiflexaceae fam. nov. - Radhey S. Gupta; Pranay Chander; Sanjan George (Antonie van Leeuwenhoek, 2013)

Variability of Altimetric Range Correction Parameters over Indian Tropical Region using JASON-1 & JASON-2 Radar Altimeters - S. Chander; Prakash Chauhan; Ajai (Journal of the Indian Society of Remote Sensing, 2012)

Agrobacterium-mediated transformation of cotyledons of mature seeds of multiple genotypes of sunflower (Helianthus annuus L.) - M. Sujatha; S. Vijay; S. Vasavi; P. Veera Reddy; S. Chander Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Development of regional wheat VI-LAI models using Resourcesat-1 AWiFS data - SASMITA CHAURASIA; R NIGAM; B K BHATTACHARYA; V N SRIDHAR; K MALLICK; S P VYAS; N K PATEL; J MUKHERJEE; CHANDER SHEKHAR; DHIRAJ KUMAR; K R P SINGH; G D BAIRAGI; et al. (Journal of Earth System Science, 2011)

Superior CMS (Ogura) lines with better combining ability improve yield and maturity in cauliflower (Brassica oleracea var. botrytis) - S. S. Dey; S. R. Sharma; R. Bhatia; Chander Parkash; R. N. Barwal (Euphytica, 2011)

Comparison of capsid gene sequences of turkey astrovirus-2 from poult-enteritis-syndrome-affected and apparently healthy turkeys - N. Jindal; D. P. Patnayak; Y. Chander; A. F. Ziegler; S. M. Goyal (Archives of Virology, 2011)

Geochemical Modeling of High Fluoride Concentration in Groundwater of Pokhran Area of Rajasthan, India - Chander Kumar Singh; Kumari Rina; R. P. Singh; S. Shashtri; V. Kamal; S. Mukherjee (Bulletin of Environmental Contamination and Toxicology, 2011)

Using molecular markers to identify two major loci controlling carotenoid contents in maize grain - Subhash Chander; Y. Q. Guo; X. H. Yang; J. Zhang; X. Q. Lu; J. B. Yan; T. M. Song; T. R. Rocheford; J. S. Li (Theoretical and Applied Genetics, 2008)

Residue Evaluation of Controlled-Release Formulations of Imidacloprid Against Rice Leaf Folder - B. Ram Prasad; Vidya S. Singh; Subhash Chander; Jitendra Kumar (Bulletin of Environmental Contamination and Toxicology, 2007)

IL-10 promoter single nucleotide polymorphisms are significantly associated with resistance to leprosy - Dheeraj Malhotra; Katayoon Darvishi; Soni Sood; Swarkar Sharma; Chander Grover; Vineet Relhan; B. S. N. Reddy; R. N. K. Bamezai (Human Genetics, 2005)

Antidyslipidemic and antioxidant activities of different fractions ofTerminalia arjuna stem bark - Ramesh Chander; Kavita Singh; A K Khanna; S M Kaul; Anju Puri; Rashmi Saxena; Gitika Bhatia; Farhan Rizvi; A K. Rastogi (Indian Journal of Clinical Biochemistry, 2004)

Behaviour of β-Cyfluthrin and Imidacloprid in Mustard Crop: Alternative Insecticide for Aphid Control - M. Gopal; I. Mukherjee; S. Chander (Bulletin of Environmental Contamination and Toxicology, 2002)

An investigation into the effect and mechanisms of action of nicotine in inflammatory bowel disease - A.P. Sykes; C. Brampton; S. Klee; C.L. Chander; C. Whelan; M.E. Parsons (Inflammation Research, 2000)

In vitro propagation of Valeriana jatamansi - R. Kaur; M. Sood; S. Chander; R. Mahajan; V. Kumar; D.R. Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Granulocyte-colony stimulating factor decreases glycosaminoglycan concentration and increases nitric oxide production in rat articular cartilage - S. Stephan; W. M. Purcell , C. L. Chander (Inflammation Research, 1999)

The ability of nicotine to induce glycosaminoglycan release in porcine nasal cartilage explant cultures - R. Misra; S. Stephan; C. L. Chander (Inflammation Research, 1999)

Soil organic matter, microbial biomass and enzyme activities in a tropical agroforestry system - K. Chander; S. Goyal; D. P. Nandal; K. K. Kapoor (Biology and Fertility of Soils, 1998)

Organic matter, microbial biomass and enzyme activity of soils under different crop rotations in the tropics - K. Chander; S. Goyal; M. C. Mundra; K. K. Kapoor (Biology and Fertility of Soils, 1997)